Notes about the evolution of anthropology in San Marcos - Martínez, Héctor (Universidad del Pacífico, 1990)
From the beginning Anthropology in San Marcos shows an unequivocal tendency to link a practical understanding of the past with the present with regard  to potential efforts at social transformation, focusing its emphasis on rural and tribal populations. In this task not linking itself exclusively to any train of thought stands out as one important characteristic. At the same time anthropology did continually nourish itself with the contributions of historians, sociologists, economists, and psychiatrists. In this regard, anthropology at San Marcos defies facile classifications culturalist, funcionalist, structuralist, or other "isms", that some are inclined to attribute to it. Presently on the strength of a rigorous self examination and the implementation of a new curriculum, anthropology is quickly coming out of the undeniable crisis in which it was immersed more than a decade, and recovering the preeminent position that it had in the past.This crisis was in part a result of the general disorder generated in the University itself, recovering, thus, the leading position it had in the past.